Impact of crop type on the greenhouse gas (GHG) emissions of a rewetted cultivated peatland - K. Lång; H. Honkanen; J. Heikkinen; S. Saarnio; T. Larmola; H. Kekkonen (SOIL)
Raising the water table is an effective way to abate greenhouse gas emissions from cultivated peat soils. We experimented a gradual water table rise at a highly degraded agricultural peat soil site with plots of willow, forage and mixed vegetation (set-aside) in southern Finland. We measured the emissions of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) for 4 years. The mean annual groundwater table depth was about 54, 40, 40 and 30 cm in 2019–2022, respectively. The results indicated that a 10 cm rise in the water table depth was able to slow down annual CO2 emissions from soil respiration by 0.87 Mg CO2-C ha−1. CH4 fluxes changed from uptake to emissions with a rise in the water table depth, and the maximum mean annual emission rate was 11 kg CH4-C ha−1. Nitrous oxide emissions ranged from 2 to 33 kg N2O-N ha−1 yr−1; they were high in bare soil at the beginning of the experiment but decreased towards the end of the experiment. Short rotation cropping of willow reached net sequestration of carbon before harvest, but all treatments and years showed a net loss of carbon based on the net ecosystem carbon balance. Overall, the short rotation coppice of willow had the most favourable carbon and greenhouse gas balance over the years (10 Mg CO2 eq. on average over 4 years). The total greenhouse gas balance of the forage and set-aside treatments did not go under 27 Mg CO2 eq. ha−1 yr−1, highlighting the challenge in curbing peat decomposition in highly degraded cultivated peatlands.